Nilai-Nilai Religius dalam Novel 172 Days Karya Nadzira Shafa - Malina, Anggia; Putra, Rio Elsa; Sunata, Ivan (Institut Agama Islam Negeri Kerinci, 2023)
The formulation of the problem in this research is what are the religious aspects contained in the Novel 172 Days by Nadzira Shafa. The aim of the research is to obtain an accurate, complete, detailed and in-depth understanding of the description of the religious aspects contained in the Novel 172 Days by Nadzira Shafa. The research method used in this research is a qualitative descriptive method which aims to describe the religious aspects contained in the novel 172 Days by Nadzira Shafa. The data analysis technique that the researcher carried out was a document/content analysis technique with steps: 1) quotations containing religious aspects in the novel 172 Days by Nadzira Shafa which had been collected were identified based on religious aspects, 2) quotations containing religious aspects grouped into one, 3) each classification of the same religious aspect is analyzed further to be described, 4) describes the religious aspects contained in the novel 172 Days by Nadzira Shafa, 5) analyzes and interprets the data by connecting the data with the theoretical basis exists to be formulated into conclusions, 6) draw conclusions. From the research results, it can be concluded that 1) the religious values ​​contained in the novel 172 Days by Nadzira Shafa have 4 religious values, namely the relationship between humans and their God, the relationship between humans and themselves, the relationship between humans and other humans, and the relationship between humans and themselves. natural. 2) based on the results of the discussion about moral values ​​above in the novel 172 Days by Nadzira Shafa, it can be concluded that moral values ​​include 4 types, namely with a total of 157 data which includes 65 data of human relationships with God, 27 data of human relationships with themselves, Human relations with other humans 64 data, and human relations with nature 2 data.